Comparison of the European and Japanese guidelines for the acute management of intracerebral hemorrhage - Toyoda, Kazunori; Steiner, Thorsten; Epple, Corina; Kern, Rolf; Nagayama, Masao; Shinohara, Yukito; Hennerici, Michael G. (Cerebrovascular diseases, 2013)
Background: Different aspects of acute stroke management and strategies for stroke prevention derive from two viewpoints: specific traditional and historical backgrounds and evidence-based medicine from modern randomized controlled trials (RCTs), meta-analysis and authorized clinical practice guidelines (GLs). Regarding intracerebral hemorrhage (ICH), Cerebrovascular Diseases published the 2006 European stroke initiative recommendations for the management of ICH. In 2009, the revised Japanese GLs for the management of stroke, including that of ICH, appeared in Japanese. Whereas GLs for the prevention and treatment of ischemic stroke were presented in detail, recommendations with regard to ICH are relatively rare both in Japan and Europe. Methods: Since 2011, the authors have met repeatedly and have compared the latest versions of published European and Japanese GLs for ischemic and hemorrhagic strokes. Many aspects have only been addressed in one but left out in the other GLs, which consequently founded the basis for the comparison. Classification of evidence levels and recommendation grades defined by the individual committees differed between both original GLs. Results: Aspects of major importance were similar and hence did not need extensive interpretation, mostly due to a lack of evidence from appropriate RCTs worldwide. The target level to which systolic blood pressure should be lowered is quite high; <170 mm Hg for patients with known hypertension in Europe and <180 mm Hg in Japan. The results of ongoing clinical trials are awaited for the optimal target level and optimal medications. Concerning ICH associated with oral anticoagulant therapy, both guidelines give similar recommendations, namely that anticoagulation should be discontinued and the international normalized ratio of prothrombin time should be normalized with prothrombin complex concentrate or fresh-frozen plasma and additional vitamin K. Patients with ICH were treated surgically, often based on individual decisions - more frequently in Japan, depending on the association with hypertension. Patients with large or intraventricular bleedings were only treated if a life-saving performance was considered, irrespective of the neurological outcome. Infra- and supratentorial differences were similarly addressed in both GLs. Conclusion: This brief survey - when compared with the lengthy original recommendations - provides a stimulating basis for an extended interest among Japanese and European stroke clinicians to learn from their individual experiences and to strengthen efforts for joint cooperation in treating and preventing stroke all around the globe.
Gesehen am 04.10.2021